Operational rate distortion theory - Sadeh, Ilan (Zielona Góra: Uniwersytet Zielonogórski)
The paper treats data compression from the viewpoint of information theory where a certain error probability is tolerable. We obtain bounds for the minimal rate given an error probability for block-coding of general stationary ergodic sources. An application of the theory of large deviations provides numerical methods to compute for memoryless sources, the minimal compression rate given a tolerable error probability. Interesting connections between Cramer's functions and Shannon's theory for lossy coding are found.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka